Penggunaan Bakteri Lactobacillus plantarum pada Silase Kulit Pisang Kepok (Musa paradisiaca L) Sebagai Pakan Ternak - Nur Kholis; Dyah Laksito Rukmi; Yuni Mariani (Jurnal Ilmu Peternakan Terapan, 2018)
This study aims to determine the effect of the use of Lactobacillus plantarum on the banana kepok silage quality. The experimental design used in this study was Completely Randomized Design (CRD) using 4 treatments and 5 replications. The treatment was silage without inoculation L. plantarum (T1), inoculation 104 CFU/ml (T2), 105 CFU/ml (T3), and 106 CFU/ml (T4). The results showed that the dry material of kepok banana peels silage was not different between treatments. The inoculation treatment of L. plantarum was able to increase (P<0.05) of crude protein and crude fat content,Â  but decrease (P<0.05) crude fiber content and pH silage. The addition of L. plantarum inoculation to kepok banana peels could improve the quality of silage as an alternative ruminant feed.Â